Pediatric COVID-19: The Silent Spreaders are Not so Silent Anymore - Dewan, Pooja; Gupta, Piyush (Annals of the National Academy of Medical Sciences (India), 2020)
The COVID-19 pandemic has been an enigma to all. Contrary to the initial perception that the novel coronavirus spares most kids, evidence has been emerging that children including neonates and infants are also infected. The clinical presentation in the pediatric age group has been reported as often atypical. Given the fact that children could be carriers of this deadly virus and hence act as spreaders, the need to recognize pediatric COVID-19 seems imminent.
Keywords: child; coronavirus; pandemic